THE INFLUENCE OF THE TOURISM SECTOR ON LOCAL REVENUE IN THE DISTRICT / CITY IN THE EX-SURAKARTA AREA IN 2017-2021 - Rezsy Herawati; Sitti Retno Faridatussalam (Jurnal Ekonomi, 2023)
The tourism sector is one of the sectors that receives top priority in order to improve that regional economic structure in the Regency/City of the Former Surakarta Residency and can increase independence and competitiveness. Thus it is expected to be able to provide a sizeable contribution to PAD. This study aims to determine the effect of Gross Regional Domestic Product, Number of National Tourists, Number of International Tourists, Number of Tourism Objects and Number of Hotels to Regional Original Income. The study was conducted in 6 Regencies/Cities in the Former Surakarta Residency in the research method used panel data regression and is estimated by Eviews 10. The research tool used is panel data regression analysis. The result of the study found that the Fixed Effect Model (FEM) estimated model was selected as the best estimation result. Number of National Tourists and Number of Tourism Objects has an influence on Regional Original Income. Meanwhile, Number of International Tourists, Gross Regional Domestic Product and Number of Hotels no influence on the Regional Original Income in the Former Surakarta Regency during the 2017-2021 period.